The Product Strategy of Afterwork Study at Masjid Al Lathiif Bandung : A Case Study - Syauqi, Rasyid Ilyasa; Herma Musyanto, Moch. (Proceedings of International Conference on Da'wa and Communication, 2023)
Abstract: Masjid Al Lathiif in Bandung is actively involved in religious and educational activities. The regular program called "Afterwork Study" is held every Monday night, covering topics such as business, motivation, daily life issues, and mental health. Experts in their respective fields conduct these sessions. This research aims to describe the product strategy implemented by the mosque in the Afterwork Study program. Qualitative methods were employed, involving data collection through observation, interviews, and documentation. The findings reveal four effective product strategy points: 1) building a strong brand identity and brand equity, 2) thoughtful packaging with consideration for value impact, 3) a focus on delivering relevant and high-quality content, and 4) providing excellent services while creating a deep connection between participants and the program. This study is expected to contribute insights into the management and marketing of religious activities in a mosque. Keywords: Al Lathiif Mosque, Afterwork, Product Strategy